Analisis Faktor-Faktor yang Mempengaruhi Minat Mahasiswa Berinvestasi di Pasar Modal Syariah - Sufiati Annisa; Ismu Hartarto; Surya Ningsih Damanik; Reni Ria Armayani Hasibuan (VISA: Journal of Vision and Ideas, 2021)
Investment is the process of saving money and putting it somewhere in the hope that it will increase in value. Many people are not familiar with the capital market, and many people who don't know much about it are more likely to invest in it and fall victim to fraud. In order to reduce fraud and feel safe when investing, the Indonesian people need to learn investment knowledge. The growth of Islamic banks has helped Islamic law develop as a part of the financial market. Although Indonesia is currently being hit by the Covid-19 pandemic, it is undeniable that the growth of the Islamic capital market in Indonesia has increased quite significantly. The Millennial generation is now looking for and trying to start investing. The millennial generation has the highest rate of unemployment of any generation in history. Keywords: investment knowledge, capital market, millennial generation